Tax-benefit systems in Europe and the US: Between equity and efficiency - Olivier Bargain; Mathias Dolls; Dirk Neumann; Andreas Peichl; Sebastian Siegloch (Center for Economic Studies and ifo Institute (CESifo), 2011)
Whether observed differences in redistributive policies across countries are the result of differences in social preferences or efficiency constraints is an important question that paves the debate about the optimality of welfare regimes. To shed new light on this question, we estimate labor supply elasticities on microdata and adopt an inverted optimal tax approach to characterize the redistributive preferences embodied in the welfare systems of 17 EU countries and the US. Implicit social welfare functions are broadly compatible with the fiction of an optimizing Paretian social planner. Some exceptions due to generous demogrant transfers are consistent with the ignorance of behavioral responses by some European governments and are partly corrected by recent policy developments. Heterogeneity in leisure-consumption preferences somewhat affect the international comparison in degrees of revealed inequality aversion, but differences in social preferences are significant only between broad groups of countries.
Keywords: H11; H21; D63; C63; 330; social preferences; redistribution; optimal income taxation; labor supply; Steuerpolitik; Sozialpolitik; Soziale Wohlfahrtsfunktion; Offenbarte Präferenzen; Optimale Besteuerung; Arbeitsangebot; EU-Staaten; USA